Results from the sowing and planting experiment of Norway spruce (Picea abies) on fertile sites in North Karelia, Finland - Kolström, Taneli (Silva Fennica, 1991)
Different methods of sowing and planting of Norway spruce ( (L.) H. Karst.) were compared on fertile sites in North Karelia (62Â°20âN, 29Â°35âE, 85â120 m a.s.l.). The planting material were 4-year-old bare-rooted transplants, 2-year-old bare-rooted seedlings, and 2-year-old containerized seedlings raised in plastic greenhouse. The sowing methods were band sowing and shelter sowing. Ground vegetation was controlled during the first growing season mechanically or chemically, or the control was omitted totally.Picea abies